Pengaruh Pengelolaan Keuangan Daerah, Akuntabilitas Dan Transparansi Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Karawang Tahun 2022 - Yunanti Eva Mandasari; Tubagus Ahmad Darojat; Nunung Nurhasanah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine and analyze the influence of financial performance on 3 SKPDs, namely the Secretariat of the Karawang Regency People's Representative Council, the Karawang Regency Regional Inspectorate and the Karawang Regency Regional Financial and Asset Management Agency in 2022 in terms of regional financial management, accountability and transparency. The sample used in this research was 3 SKPD employees with a total of 99 out of a total population of 187 employees. The data analysis method used is a descriptive verification method using primary data types and an analysis method using path analysis. The results of research on correlation analysis show that there is a significant relationship between regional financial management and accountability but has a low level of relationship, there is a significant relationship between accountability and transparency but has a low level of relationship and there is no significant but positive relationship between regional financial management with transparency because it has a very low level of relationship. Meanwhile, the results of path analysis research show that regional financial management partially influences the regional financial performance of Karawang Regency because it has an influence of 13.64%, accountability partially influences the regional financial performance of Karawang Regency because it has an influence of 5.63% and transparency partially influences the regional financial performance of Karawang Regency because it has an influence of 8.55%. Based on the overall results, it shows that regional financial management, accountability and transparency simultaneously influence the regional financial performance of Karawang Regency because it amounts to 27.8% while the remaining 72.2% is the contribution of other variables not studied (ԑ).